Carbon-Based Nanomaterials for Biomedical Applications: A Recent Study - Maiti, Debabrata; Tong, Xiangmin; Mou, Xiaozhou; Yang, Kai (Frontiers in Pharmacology, 2019)
The study of carbon-based nanomaterials (CBNs) for biomedical applications has attracted great attention due to their unique chemical and physical properties including thermal, mechanical, electrical, optical and structural diversity. With the help of these intrinsic properties, CBNs, including carbon nanotubes (CNT), graphene oxide (GO), and graphene quantum dots (GQDs), have been extensively investigated in biomedical applications. This review summarizes the most recent studies in developing of CBNs for various biomedical applications including bio-sensing, drug delivery and cancer therapy.